PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY DENGAN LKPD BERBASIS SCAFFOLDING UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS SISWA - Dyah Puspita Ningrum; Mohammad Budiyanto; Enny Susiyawati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to describe the achievements for VIII A students of JHS 1 Kraksaan in improving science process skills on the matter of Archimedes Principle through the implementation of a guided inquiry learning model with scaffolding student’s worksheet. One-Group Pre-test-Post-test design is used with a total 30 students in one class. The instrument in data was in the sheets of learning plan, sheet of pre-test and post-test science process skills, and questionnaires to determine student responses from learning activities. The results of data analysis showed that: (1) The learning plan use guided inquiry learning model with scaffolding student’s worksheet to train student’s science process skills on the matter of Archimedes Principle was done very well. (2) Science process skills of students are increased with the N-gain score obtained of 0.69 with a medium category. (3) The result of student responses is 92,31% of students provide a positive responses with a very good category, so the implementation of guided inquiry learning model with scaffolding student’s worksheet can train student’s science process skills on the matter of Archimedes Principle.